Analisis Pengaruh Lingkungan Kerja Terhadap Peningkatan Kinerja Karyawan Pada PT. Heulang - Rennie Rennie; Sri Sundari; Marisi Pakpahan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Employee performance refers to the abilities, skills and work results demonstrated by an employee in carrying out their duties and responsibilities. This includes the extent to which an employee is successful in achieving the goals and standards that have been set, both in terms of quality and quantity. Employee performance can also be influenced by various factors, including work environment, job satisfaction, and other personal factors. The aim of this research is to examine and analyze the influence of the work environment on employee performance which is mediated by employee job satisfaction at PT. Heulang. The research subjects were all employees of the production department of PT. Heulang with 115 employees. The method used in this research is quantitative causality research using saturated sampling techniques. Data collection was carried out using a questionnaire that had been tested by SEM PLS. The results of this research show that the work environment has a significantly positive effect on employee performance, apart from that the work environment also mediates employee job satisfaction which can influence employee performance.